Trends and Future Perspectives in Business Intelligence - Stojanovic, Romana (Digital Repository of Theses, 2025)
Some of the global companies leverage Business Intelligence (BI) trends daily in their strategies and operations, in order to improve their business. With a unique approach to the topic, this research helped to fill the existing literature gap by giving a comprehensive research on BI and its trends. Research succeeded to provide a descriptive analysis of BI trends and identified some of the future perspectives in Business Intelligence. The observation of multiple global-sized companies helped to understand the importance of data for large organizations, and also led to the creation of comparative analysis of BI trends showing exactly how specific companies leverage specific trends for the their benefit. The most prominent trend leveraged by large companies seems to be Big Data due to immense amounts of data available nowadays. Also evidently, with that amount of data, AI is becoming crucial and inevitable part of Business Intelligence. In conclusion, new technologies are developing daily and the advancements in that area have great impact on Business Intelligence and will continue to influence future perspectives of BI trends. Further research should address new emerging trends and their challenges. In addition, further research on this topic is recommended, but should be adapted to companies of different sizes (small and/or medium).